THE ROLE OF IDIOMS IN ENHANCING BUSINESS COMMUNICATION: A STUDY ON THE USAGE OF IDIOMS IN BUSINESS LETTERS - Ataeva, Gulchekhra (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article provides a brief overview of a study on the usage of idioms in business letters. The study employed a literature review, analyzed business letters, and conducted a survey to identify the key benefits and drawbacks of using idioms in business letters, as well as the factors that influence their appropriateness. The results revealed that while idioms can make business letters more interesting and engaging, overusing or misusing them can lead to confusion. Appropriateness depends on several factors, including the reader's culture and language, the context, and the purpose of the letter. The study suggests guidelines for using idioms judiciously and appropriately to enhance the effectiveness of business communication. The findings can inform business communication practices, helping writers create more effective and engaging business letters.